2002
DOI: 10.1007/s101030200031
|View full text |Cite
|
Sign up to set email alerts
|

Laser Stimulation on Bone Defect Healing: An In Vitro Study

Abstract: The aim of this in vitro study was to evaluate whether low-power laser (LPL) stimulation can accelerate bone healing. Bone defects of a standard area were created in the distal epiphysis of 12 femora explanted from six rats, and they were cultured in BGJb medium for 21 days. Six defects were treated daily with Ga-Al-As, 780 nm LPL for 10 consecutive days (lased group, LG), while the remainder were sham-treated (control group, CG). Alkaline phosphatase/total protein (ALP/TP), calcium (Ca), and nitric oxide (NO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 17 publications
7
36
0
7
Order By: Relevance
“…3 Newly formed bone in the defects of the treatment groups presented as mean percentages and standard errors (groups connected by bars are not significantly different) seeking to show that this kind of treatment could be feasible and could be standardized in a new faster easily applied protocol. In the present study, when the laser was applied alone, the presence of organizing connective tissue, with blood capillaries and fibroblasts was observed, a result similar to those of others [17,[24][25][26]. Small amounts of trabecular bone were also observed, as found by Gerbi et al [21], indicating acceleration of the tissue repair process, as reported by Ozawa et al [2], who found an increase in cell proliferation and differentiation after laser irradiation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3 Newly formed bone in the defects of the treatment groups presented as mean percentages and standard errors (groups connected by bars are not significantly different) seeking to show that this kind of treatment could be feasible and could be standardized in a new faster easily applied protocol. In the present study, when the laser was applied alone, the presence of organizing connective tissue, with blood capillaries and fibroblasts was observed, a result similar to those of others [17,[24][25][26]. Small amounts of trabecular bone were also observed, as found by Gerbi et al [21], indicating acceleration of the tissue repair process, as reported by Ozawa et al [2], who found an increase in cell proliferation and differentiation after laser irradiation.…”
Section: Discussionsupporting
confidence: 92%
“…Histomorphometric analysis revealed that defects of group 3 (laser and pure rhBMP-2) showed the greatest area of bone formation. The use LLLI for different treatments and indications, such as pain control and tissue recovery, including mineralized tissues, has been reported [17,18]. BMPs, especially the BMP-2, have osteoinductive properties, causing mesenchymal cells to differentiate into osteoblastic cells [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Suas possíveis aplicações clínicas, como modalidade terapêutica, em lesões de partes moles e de tecido ósseo, têm sido largamente estudadas. Conquanto não exista consenso com relação aos efeitos biológi-cos do LBE no processo de reparo ósseo, seu uso parece promissor no manejo adjuvante de lesões de tecidos moles, associadas ou não à fratura (1)(2)(3)(4)(5)(6)(7)(16)(17) . Seu efeito bioestimulante, que ocorre localmente, por aumento do metabolismo celular e por redução da resposta inflamatória, está diretamente associado ao estímulo da função mitocondrial e das células do sistema fagocítico mononuclear (3,6) .…”
Section: Discussionunclassified
“…Although the specific mechanism remains unknown, laser-induced intracellular generation of reactive oxygen species probably involves energy transfer from PPIX and other photoacceptors present in the cell. In addition, several groups have described cellular functions mediated by nitric oxide (NO), which is upregulated by laser irradiation, as well as by inducible nitric oxide synthase (iNOS) [79,[81][82][83][84]. The mechanism of laser-induced control of cellular functions is believed to hinge on the regulation of photoacceptor activity and the intracellular levels of reactive oxygen species.…”
Section: Redox Pathwaysmentioning
confidence: 99%